The Routledge Companion to Performance Philosophy - Cull Ó Maoilearca, Laura; Lagaay, Alice (Taylor & Francis, 2020)
"The Routledge Companion to Performance Philosophy is a volume of especially commissioned critical essays, conversations, and collaborative, creative and performative writing mapping the key contexts, debates, methods, discourses and practices in this developing field. Firstly, the collection offers new insights on the fundamental question of how thinking happens: where, when, how and by whom philosophy is performed. Secondly, it provides a plurality of new accounts of performance and performativity - as the production of ideas, bodies and knowledges in the arts and beyond. Comprising texts written by international artists, philosophers and scholars from multiple disciplines, the essays engage with questions of how performance thinks and how thought is performed in a wide range of philosophies and performances, from the ancient to the contemporary. Concepts and practices from diverse geographical regions and cultural traditions are analysed to draw conclusions about how performance operates across art, philosophy and everyday life. The collection both contributes to and critiques the philosophy of music, dance, theatre and performance, exploring the idea of a philosophy from the arts. It is crucial reading material for those interested in the hierarchy of the relationship between philosophy and the arts, advancing debates on philosophical method, and the relation between Performance and Philosophy more broadly."